Vygotsky and sociology - Daniels, Harry (Routledge, 2012)
"Building on earlier publications by Harry Daniels, Vygotsky and Sociology provides readers with an overview of the implications for research of the theoretical work which acknowledges a debt to the writings of L.S. Vygotsky and sociologists whose work echoes his sociogenetic commitments, particularly Basil Bernstein. It provides a variety of views on the ways in which these two, conceptually linked, bodies of work can be brought together in theoretical frameworks which give new possibilities for empirical work. This book has two aims. First, to expand and enrich the Vygotskian theoretical framework; second, to illustrate the utility of such enhanced sociological imaginations and how they may be of value in researching learning in institutions and classrooms. It includes contributions from long-established writers in education, psychology and sociology, as well as relatively recent contributors to the theoretical debates and the body of research to which it has given rise, presenting their own arguments and justifications for forging links between particular theoretical traditions and, in some cases, applying new insights to obdurate empirical questions. Chapters include: Curriculum and pedagogy in the sociology of education; some lessons from comparing Durkheim and Vygotsky -- Dialectics, politics and contemporary cultural-historical research, exemplified through Marx and Vygotsky -- Sixth sense, second nature and other cultural ways of making sense of our surroundings: Vygotsky, Bernstein, and the languaged body -- Negotiating pedagogic dilemmas in non-traditional educational contexts -- Boys, skills and class: educational failure or community survival? Insights from Vygotsky and Bernstein."--Provided by publisher.